Effect of Spiritual Health and Resilience on Aggressiveness in a Sample of Active Christian Young Adults - Badilla Torres, Ruth Priscila; Moroni, Carlos Marcelo; Covarrubias, Zandra; Rodríguez, Raúl (Actualidades en Psicología, 2024)
Objective. This study evaluated the adequacy of a structural equation model examining the relationship between spiritual health, resilience, and aggressiveness. Method. Four hundred young individuals (aged 18-30) from Costa Rica and Mexico (66.5% females, 33.5% males) actively involved in religious congregations completed Spiritual Health, Mexican Resilience, and Aggression Questionnaire scales. Data was analyzed using a structural equation model. The analysis revealed a statistically significant but suboptimal fit (χ2 = 224.333, df = 51, p < .001). Nevertheless, the estimated fit indices exhibited reasonably satisfactory fit (CFI = .912, TLI = .886, RMSEA = .092, SRMR = .060). Results. Spiritual health positively affects resilience and negatively affects aggressiveness, while resilience negatively impacts aggressiveness. Consequently, fostering spiritual health may enhance the positive response in challenging situations.